Corrigendum: Second harmonic spectroscopy to optically detect valley polarization in 2D materials (2017 2D Mater. 4 021027). (19th June 2017) - Hipolito, F; Pereira, Vitor M
Abstract: This corrigendum amends typing errors in two equations in the original manuscript. These corrections do not impact any of our results, plots, statements, or conclusions.